Meningkatkan Kesejahteraan Karyawan Melalui Manajemen Produksi Perusahaan - RACHMAWATY, AYU; ROSADIANA, ALFIRA (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
This research analyzes how each company must have its own goals to achieve the progress and success of the company itself. To achieve the desired goals, good and proper management is needed to facilitate a company’s success. With effective and efficient management, a company can balance everything for the welfare and common goals. If it has achieved common goals, then it is certain that the company will be successful and run well. Based on these objectives, researchers use the literature search method and search for relevant sources. In obtaining the data and information needed, researchers conduct a literature study first as a consideration and additional insight and require reference data as a reference for writing.